Family formation and everyday travel in Britain since c.1850. Issue 2 (3rd April 2018) - Pooley, Colin G.; Jones, Tim; Jones, Heather; Spencer, Ben; Chatterjee, Kiron
Abstract: This paper focuses on the extent to which everyday travel behaviour in Britain changes in relation to family responsibilities, and examines how this has altered over the past century and a half. It is argued that prior to the mid-twentieth century changes in the family such as increased child-care responsibilities barely influenced the modes of transport used for everyday travel, but that increasingly in the later twentieth century people adjusted their travel behaviour during the family formation phases of the life cycle. In particular, parents of young children have become more car-dependent and less likely to walk or cycle. Data are drawn from two separate projects, one that collected travel life histories from the past half-century as context for research on cycling in later life, and one that uses personal diaries to reveal everyday mobility strategies of people in the nineteenth and early twentieth centuries. It is argued that the observed changes are due not only to increased access to a wide range of different transport forms, especially the motor car, but also to changes in societal perceptions of risk and norms of travel behaviour. In conclusion, it is suggested that more awareness of past travel behaviours could aid the development and implementation of more sustainable transport policies in the UK.